Outcome of minimally invasive transforaminal lumbar interbody fusion for the treatment of low grade (grade I and II) spondylolisthesis in obese patients - Islam, Anowarul; Ahmed, Zafri Ahmed; Sarker, Sagor Kumar; Hasan, M. Sariful; Rahman, A. H. M. Masiur; Rahim, Khandoker Abdur (International Journal of Research in Orthopaedics, 2025)
Background: Spondylolisthesis in obese patient is one of the causes of back pain, severe morbidity, and impairment. This study examines low-grade spondylolisthesis patients’ pain relief, functional improvement, fusion rates, and complications after minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Methods: This study was conducted in the Department of Orthopedic Surgery at BSMMU, Dhaka, from July 2023 to June 2024. 30 low-grade spondylolisthesis patients were included according to selection criteria. Functional outcomes were assessed by Visual Analogue Scale score, Oswestry disability index, Modified Macnab’s Criteria. Interbody fusion was evaluated by Bridwell interbody fusion grading system and also perioperative events were noted. Mean, standard deviation, Frequency and percentage were used to test qualitative data with chi-square. SPSS 26 data analyses will consider p-values <0.05 significant. Results: 23.33% patients were day laborer and housewives. Most commonly involved level was L5/S1 (60%), followed by L4/L5, (40 peri-operative complications were seen in 4 (13.33%) patients where in 2 (6.67%) patients had seroma, 1(3.33%) patient had discitis and 1(3.33%) patient had foot drop. One patient had discitis and 1 patient had foot drop. VAS score and Oswestry Disability Index Score had showed significant improvement in post-operative follow up (at 6 months) compared to pre-operative status (p<0.05). Overall, excellent improvement was seen in 40% of cases according to modified Macnab’s criteria on 6 months of post-operative follow up. Conclusions: MIS TLIF is a safe, efficient, and cost-effective technique when performed accurately. The reduced surgical invasiveness, shortened hospital stay, and rapid return to employment represent substantial advantages of MIS TLIF.